An analysis of the angiogenic properties of borate bioactive glasses supplemented with zinc and copper - Moll, Maximilian N.; Arango-Ospina, M; Kunisch, Elke; Walker, Tilman; Renkawitz, Tobias; Boccaccini, AR; Westhauser, Fabian (Journal of biomaterials applications, 2025)
In bone tissue engineering (BTE), vascularization can be attracted by application of biomaterials with pro-angiogenic properties like bioactive glasses (BGs). By releasing ions with angiogenesis stimulating activity including boron, zinc or copper, the angiogenic properties of BGs can be enhanced. Borate BGs like the 1393-B3 BG (composition in wt%: 56.6 B2O3, 18.5 CaO, 11.1 K2O, 5.5 Na2O, 4.6 MgO, 3.7 P2O5) constitute an attractive vector to be doped with further pro-angiogenic ions. In this study, the cytocompatiblity and the angiogenic properties of 1393-B3-BG and its copper and/or zinc-doped variants (exchange for CaO) namely B3-Cu BG (wt%: 15.5 CaO, 3.0 CuO), B3-Zn BG (wt%: 17.5 CaO, 1.0 ZnO) and B3-Cu-Zn BG (wt%: 14.5 CaO, 3.0 CuO, 1.0 ZnO) have been evaluated using human bone-marrow derived mesenchymal stromal cells (BMSCs), a human umbilical vein endothelial cells (HUVEC)-tube formation and a chorioallantoic membrane (CAM) assay. All BGs showed excellent cytocompatibility and enhanced the mRNA and protein levels of angiogenesis stimulating factors like VEGF-A. The BGs also enhanced the formation of a tubular network in the HUVEC-based assay and vascularization on the CAM. However, the addition of copper and zinc did not yield an improvement in the enhancement of angiogenesis by the 1393-B3 BG. In conclusion, in the present experimental setting, the unmodified 1393-B3 BG has demonstrated excellent cytocompatibility and strong pro-angiogenic effects with no additional benefit from incorporating zinc or copper in its composition.
Vorab online veröffentlicht: 8. Dezember 2025
Gesehen am 25.02.2026